Tindak Tutur Ekspresif pada Saluran Youtube "Qalby Etmaan" - Husnul Raja; Baso, Yusring Sanusi; Ahmad, Fadlan (Jurnal Sarjana Ilmu Budaya, 2024)
Qalby Etmaan YouTube channel serves as a digital platform presenting a variety of humanitarian programs in Arab countries. The aim of this research is to examine the form and function of expressive speech acts as proposed by Searle by using the YouTube channel "Qalby Etmaan" as the object of this study. Employing the theoretical framework of SPEAKING by Dell Hymes, the research concentrates on the analysis of situation, participants, purpose, act sequence, key, instrumentalities, norms, and genre within expressive speech acts. Data collection techniques include observation-note-taking and documentation. The research methodology is qualitative descriptive analysis, involving data collection from transcripts of dialogues in the channel's videos, followed by an analysis considering keywords, expressions, and expressive nuances reflecting the functions of expressive speech acts in various contexts. The results reveal a diverse range of expressive speech acts, such as acts of apologizing, expressing gratitude, greeting, condolence, and congratulating. In the function of apologizing, there is a direct use of apology expressions, both as the beginning or end of a conversation, as well as expressions of solidarity in grief. In the function of expressing gratitude, there are direct expressions of thanks that reflect belonging and solidarity, as well as expressions laden with cultural and religious values. The function of welcoming includes greetings, welcoming expressions, inquiring about the condition and health, and positive responses and prayers. In the function of condoling, there are expressions of hope and patience, as well as expressions of prayer. In the function of congratulating, there are expressions of joy and happiness for someone's achievement. Keywords: Speech Acts, Expressive Speech Acts, YouTube